1987
DOI: 10.1063/1.866198
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric magnetic flux generation, m=1 activity, and edge phenomena on a reversed-field pinch

Abstract: The ZT-40M [Fusion Tech. 8, 1571 (1985)] reversed-field pinch has been used to study magnetic flux perturbations during high-θ [θ=Bθ(a)/〈Bφ〉>1.6] discharges. Asymmetric toroidal magnetic flux perturbations are found to be associated with magnetic flux emerging through the toroidal shell gap and with m=0 magnetic disturbances moving toroidally. Ramping current discharges, which are a special case of high-θ operation, show the most robust self-generation of toroidal flux. The electron density fluctuations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
25
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 24 publications
9
25
0
Order By: Relevance
“…This can be explained by the above scenario that the m=O mode grows as a result of the nonlinear coupling of the m=l modes, and agrees well with the recent experimental observation. 19 > The dashed lines in the figures for W and F denote the simulation results for the case in which the perturbations (m; n)=F(O; 0) are excluded at time t=lOOrA. In this case the time development of the system is governed solely by the dissipation process, no relaxation process coming into play.…”
Section: Simulation Study Of the Nonlinear Dynamics In Rfpmentioning
confidence: 97%
“…This can be explained by the above scenario that the m=O mode grows as a result of the nonlinear coupling of the m=l modes, and agrees well with the recent experimental observation. 19 > The dashed lines in the figures for W and F denote the simulation results for the case in which the perturbations (m; n)=F(O; 0) are excluded at time t=lOOrA. In this case the time development of the system is governed solely by the dissipation process, no relaxation process coming into play.…”
Section: Simulation Study Of the Nonlinear Dynamics In Rfpmentioning
confidence: 97%
“…Magnetic fluctuations play a substantial role in the global dynamics of the RFP and much work has been carried out previously to characterize magnetic tearing mode behavior in the RFP. 5,[27][28][29][30][31][32][33] Direct measurements of the tearing mode spectrum in the core of MST are not available for any quantity, including magnetic fields. Nevertheless, magnetic mode spectral mea- surements are routinely made at the plasma wall by arrays of magnetic coils.…”
Section: B Extracting Tearing Mode Flowsmentioning
confidence: 99%
“…29 The observations of discrete relaxation in the RFP plasmas showed that the relaxation may go on in an oscillatory manner. The loop voltage, reversal parameter, and electron current all have sawtooth character [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] during the relaxation. The loop voltage and fluctuation amplitudes peak at the sawtooth crash.…”
Section: Jϭ"؋bϭb ͑1͒mentioning
confidence: 99%
“…63. Since the MHD dynamo action was introduced into the RFP plasma, 55 the MHD dynamo theory has enjoyed considerable success in the physics of the laboratory plasma and is well supported by the experimental phenomenology [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] and the numerical simulations. 66 -77 It is of great importance to the physics of the RFP plasma that the MHD dynamo electric field and mean-field Ohm's law have been verified in the recent experiment.…”
Section: Jϭ"؋bϭb ͑1͒mentioning
confidence: 99%
See 1 more Smart Citation